Economic integration in Africa - Robson, Peter (Allen & Unwin LondonGB, 1968)
Examines the economics of integration, with special reference to less developed countries. Considers some salient features of the African economy setting within which actual and projected schemes must operate. Surveys the experience of existing economic arrangements for economic integration between independent African states.